Повсякденне життя та професійна діяльність скульпторів Львова другої половини XVIII ст. - Лильо, О.М. (Український історичний журнал, 2017)
Історія розвитку культурно-мистецького осередку Львова XVIII ст. все ще недостатньо досліджена. На сьогодні історіографія проблеми представлена обмеженою кількістю праць, де робляться спроби оцінити творчість окремих митців. У статті ставиться завдання заповнити прогалини з названої тематики, висвітлити головні аспекти в розвитку середовища майстрів скульптури Львова. The history of cultural and artistic city center in the 18 century belongs to the list of unexplored problems in modern historical research. Currently there are a limited number of studies, which attempt to investigate works and activity of L’viv artists. The subject of research is activity of the circle of L’viv sculptors in the second half of the 18 century. This article aims to fill the research and highlight the main aspects in the development of L’viv cultural environment in the outlined period.